2022
DOI: 10.3389/feart.2021.787222
|View full text |Cite
|
Sign up to set email alerts
|

Study on Chemical Genesis of Deep Geothermal Fluid in Gaoyang Geothermal Field

Abstract: Geothermal resources are clean energy with a great potential for development and utilization. Gaoyang geothermal field, located in the middle of the raised area in Hebei province, China, is one of the three major geothermal fields in the Xiong’an New Area. With the development of the Xiong’an New Area, this geothermal field has become a research hotspot. According to the latest survey, the bottom-hole temperature of the D34 and D35 areas in the north of Gaoyang geothermal field is 149°C and 116°C, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The source of Na and Si is commonly attributed to sodium feldspar and/or rhyolite hydrolysis by hydrogen ions donated by bicarbonate dissociation (Sharp and Tranter, 2017;Absametov et al, 2023). Such silicate dissolution is also documented elsewhere in hydrothermal systems (Shoedarto et al, 2022;Xing et al, 2022). Shoedarto et al (2022) showed silicate weathering dominates water-rock interaction in hot springs in Southern Bandung, West Java, Indonesia.…”
Section: The Upper Cretaceous Aquifermentioning
confidence: 91%
“…The source of Na and Si is commonly attributed to sodium feldspar and/or rhyolite hydrolysis by hydrogen ions donated by bicarbonate dissociation (Sharp and Tranter, 2017;Absametov et al, 2023). Such silicate dissolution is also documented elsewhere in hydrothermal systems (Shoedarto et al, 2022;Xing et al, 2022). Shoedarto et al (2022) showed silicate weathering dominates water-rock interaction in hot springs in Southern Bandung, West Java, Indonesia.…”
Section: The Upper Cretaceous Aquifermentioning
confidence: 91%
“…The hydrogen and oxygen isotope characteristics of groundwater can be used to judge the origin of groundwater, determine the recharge conditions of groundwater, the relationship between atmospheric precipitation and surface water and groundwater, and understand the circulation path of groundwater [22,[31][32][33]. The mean δ 2 H vsmow values of low-, medium-and high-temperature groundwater in the region showed a decreasing trend: −77.39 ± 1.05‰ > −83.06 ± 0.86‰ > −86.99 ± 0.8‰.…”
Section: Source Of Supplymentioning
confidence: 99%
“…Studies on the distribution of environmental isotopes and hydrochemistry, including 14 C, can clarify key geothermal cycle information such as residence time and circulation depth of conductive geothermal fluids in subsidence basins in the Gansu region [20]. In addition, various temperature scale calculations and scaling corrosion studies of geothermal water can evaluate the amount of geothermal resources and their availability in the region [21,22]. These previous works provide a research basis for exploring the geochemical origin of geothermal fluids, evaluating the quality of geothermal and related mineral resources, the thermodynamic activities and internal rheology of the relevant Earth's crust.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, magmatic activity is intense and accompanied by hydrothermal dissolution. The supergenetic karst formed at this time is the most conducive to reservoir construction, and the karst types mainly include weathering karst zone, fault karst zone and bedding karst zone (Xing et al, 2022).…”
Section: Geological Settingmentioning
confidence: 99%